PENGARUH LATIHAN BERLARI ZIG-ZAG MELEWATI CONE MENGGUNAKAN BOLA TERHADAP KEMAMPUAN DRIBBLING PEMAIN SSB UNRI - Randa Saputra Alcahyadi; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of observations in the field it is known that there are many deficiencies that occur in the Unri Pekanbaru SSB Team influenced by technical factors, such as dribbling. Many athletes who, when dribbling too far away from their feet and are not supported by a zig-zag run that looks stiff, makes it easy for the opponent to grab the ball, this has an impact on the team's appearance. pretest dribbling test (Marjohan, 2004: 145), After that the sample was given a training program Running Zig-Zag Through Cone Using the Ball for 16 meetings. After that, the Posttest dribbling test is done. The data obtained were analyzed descriptively, then further testing of the research hypotheses that had been submitted was according to the problem, namely: "there was the effect of the Zig-Zag Running exercise through the Cone Using Ball (X) Against Dribbling (Y). Based on the results of the analysis of the t test yielding a Tcount of 10.65 and Ttabel 1.761. It means that Thitung> T table, statistical data analysis there is an average pree-test of 18.55 and after being given training 16 times with a frequency of 3 times a week the post-test average is 17.86 T test after calculating the basis there are increasing numbers of differences or an increase of 0.96, it can be concluded that the ability of influential players with Zig-Zag Running Exercises Passing Cones Using Balls is needed to support frequency when doing exercises in increasing Dribling results. it can be summarized as follows: There is a significant effect between Zig-Zag Running Exercises Passing Cone Using Ball (X) with Dribbling (Y) on Unri Pekanbaru SSB Players Key Words: Zig-Zag Running Practice, Dribbling Ability